2021
DOI: 10.4314/njp.v48i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of breastfeeding practices among mothers in a developing African country – A tertiary facility based study in Calabar, Nigeria

Abstract: Introduction: Breastfeeding is essential for optimum childhood development. Although there is an increased awareness of the importance of breast milk, the Nigerian Demographic and Health Survey of 2018 showed that less than one-third (29%) of mothers in Nigeria practice exclusive breastfeeding. This may be attributed to several factors, hence the need for this study to assess the indicators and predictors of breastfeeding practices among mothers in a tertiary facility in Calabar, Cross River State. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
2
2
Order By: Relevance
“…Less than half (45.5%) of the mothers in this study put their babies to breast within 1 h after delivery. This is similar to the average national rate of 42.1% reported in the Nigeria Demographic and Health Survey 7 as well as another report from South–south Nigeria (44.6%), 21 but lower than the rates observed in Ghana (63.4%), Bangladesh (67%) and Uganda (68%) 22–24 . The differences noted may be related to the practices of the healthcare workers at the delivery centres, in addition to other factors such as neonatal and maternal health status 24 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Less than half (45.5%) of the mothers in this study put their babies to breast within 1 h after delivery. This is similar to the average national rate of 42.1% reported in the Nigeria Demographic and Health Survey 7 as well as another report from South–south Nigeria (44.6%), 21 but lower than the rates observed in Ghana (63.4%), Bangladesh (67%) and Uganda (68%) 22–24 . The differences noted may be related to the practices of the healthcare workers at the delivery centres, in addition to other factors such as neonatal and maternal health status 24 …”
Section: Discussionsupporting
confidence: 91%
“…Less than half (47.3%) of the mothers in this study practised exclusive breastfeeding for 6 months. This exclusive breastfeeding rate is higher than the 29% reported by the Nigeria Demographic and Health Survey 7 but lower than some other Nigerian reports 21,25 . The observed rate is also at variance with other African, Asian and European studies which mostly reported lower rates 26–28 .…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Early initiation of breastfeeding within one hour of birth in this study was observed in 72.4% of infants. This rate is higher than the United Nations Children’s Fund (UNICEF) global database rate of 45% [ 11 ], the South African rate of 63% based on the 2015 UNICEF data [ 10 ], and the rate of 44.6% in Calabar, Nigeria [ 12 ]. This high rate shows that there is an increase in the awareness and importance of breastfeeding among mothers of infants studied.…”
Section: Discussionmentioning
confidence: 99%
“…Kruger et al [ 8 ] and MacIntyre et al [ 13 ] documented the commencement of complementary food as early as one month and six weeks of life, respectively, in South Africa. Ikobah et al [ 12 ] documented an early commencement of complementary food at one month of life in Calabar, Nigeria. Studies in Tanzania [ 14 ], Kenya [ 15 ], and Malawi [ 16 ] have shown early commencement of complementary feed at ages 2-3 months of life.…”
Section: Discussionmentioning
confidence: 99%